Three‐Dimensional Visualization of Subcellular Dynamics of Cancer Cell Destruction on Therapeutic Nanodrug Treatment. Issue 7 (13th July 2021) - Raveendran, Sreejith; Sen, Anindito; Maekawa, Toru; Kumar, D. Sakthi
Abstract : Multi‐Modal Targeting Strategy for Breast Cancer In article number 2000145 by Sreejith Raveendran, D. Sakthi Kumar and co‐workers, a multi‐modal targeting strategy for breast cancer using combinatorial nanodrug complex is studied and ultra‐structural visualization of subcellular targeting and multiple parallel damage caused to breast cancer cells are demonstrated using serial‐block‐face scanning electron microscopy. Mechanistic and conformational understanding of specific subcellular connections of novel smart nanocarriers with various intrinsic receptors are critical for the design and delivery of novel cancer therapeutics.